The Effects of Non-Digital Game-Based Learning on Brunei Darussalam Students’ Mathematical Perspectives and Achievements - Nurul Aqilah Mohd. Yusof; Masitah Shahrill (SEAMEO Regional Centre for QITEP in Mathematics, 2021)
The purpose of this study is to investigate the effectiveness of a non-digital game based learning approach by assessing the differences in students’ achievement score between the pre-test and the post-test on the topic of multiplication and division with indices. A paired sample t-test was used to investigate a significant difference in the students’ achievements after implementing the non-digital game-based learning intervention. A total of 35 students from two classes of nine grade students in one of the secondary schools in Brunei Darussalam was involved in the study. Another aim of this study was to investigate the students’ perspectives on using a non-digital game-based learning approach in their learning process. This was analysed through the questionnaire and interviews. The results showed that the integration of a non-digital game-based learning approach in the mathematics lesson did have a positive effect on the students’ achievement scores. More than half of the students believed that the game has helped them to improve their Mathematical skills.